The Existence of Accrual Anomaly Phenomena in Indonesia Capital Market - Gerrinko Giffari Wurintara; Hamidah Hamidah (Journal of Accounting and Investment, 2020)
Research aims: Sloan (1996) finds that investors mispriced the stock. They could not detect differences in earnings persistence. Such a phenomenon is called an accrual anomaly. This study aims to find out the existence of accrual anomalies in the Indonesian capital market.Design/Methodology/Approach: The accrual anomaly phenomenon is supported by testing whether there is a negative effect between accrual and abnormal returns. The research sample consisted of manufacturing companies from 2014 - 2017, which were tested using the Ordinary Least Square.Research findings: First, the results show that the company’s accrual rate negatively influenced the abnormal returns, both before and after the use of control variables. Second, this article also discovered that companies having low accrual rates were consistent over four years and had greater returns compared to companies with high accrual rates.Theoretical contribution/ Originality: This article contributes to financial literacy and accounting, especially to the theory of efficient market hypotheses. There was evidence of accrual anomalies indicating that the Indonesian capital market was inefficient.Practitioner/Policy implication: Indeed, the results of this study contribute to investors and financial analysis to consider and reevaluate their long-term investment strategies in purpose to avoid mispricing in the earnings component.Research limitation/Implication: This research is inseparable from limitations, one of which is the presence of shares that were not actively traded in the study sample. Second, this article only used a sample of companies that did not experience a loss.